THE RELATIONSHIP BETWEEN HEALTH BELIEF AND DENGUE HEMORRHAGIC FEVER PREVENTION OF FAMILY HEALTH LEADERS, NONG BUA SALA SUB-DISTRICT, MUEANG DISTRICT, NAKHON RATCHASIMA PROVINCE - PromJan , Theerapong (Primary Health Care Journal (Northeastern Edition), 2022)
The purpose of the descriptive study is to study the relationship between health beliefs and dengue hemorrhagic fever prevention of family health leaders. By systematic sampling, the sample was 327 family health leaders, Nong Bua Sala sub-district, Mueang district, Nakhon Ratchasima province. The data was collected by questionnaire. The data were analyzed by frequency, percentage, mean, standard deviation, the maximum score and the minimum score, Chi-Square, and Pearson correlation coefficient. The result of the study revealed that the majority was 59.6% male, the average age was 44.76 years old, the age was between 50-59 years old was 33.0% the marital status was 68.5%, the education level was primary at 57.8%, the agriculture was 49.9% and used to join the activity of dengue hemorrhagic fever prevention was 80.1%. The sample group perceived barriers to dengue hemorrhagic fever were at the moderate level of 53.5% and 48.0%. Perceived severity of dengue hemorrhagic fever prevention and perceived benefit in dengue hemorrhagic fever prevention were at the high level of 72.5% and 66.9%. The behavior in dengue hemorrhagic fever prevention was at the high level of 51.7%. The perceived barrier in dengue hemorrhagic fever prevention, perceived benefit in dengue hemorrhagic fever prevention, and perceived severity of dengue hemorrhagic fever had a positive relationship with the behavior in dengue hemorrhagic fever prevention of family health leaders with statistical significance (r = .264, .219, and .061, P-value < .05). Perceived risk of dengue hemorrhagic fever had a negative relationship with the behavior in dengue hemorrhagic fever prevention of family health leaders with statistical significance (r =-.228, P-value < .05).